Innovations and reflections on education and research in the university context (Revista Lusófona de Educação, 2025)
Higher education, as a field of innovation and transformation, is constantly evolving, driven by new pedagogical approaches and emerging technologies. In this issue of the Revista Lusófona de Educação, we present a selection of articles that delve into crucial themes for educational practice and academic training in the global context. The contributions explore topics such as artificial intelligence in higher education, co‑regulation of learning, emotional recognition in education, and cognition in mathematics curricula. They also offer reflections on influential figures like Paulo Freire and Amílcar Cabral, alongside a critical analysis of pedagogy. Collectively, the articles surface debates that are highly relevant to pedagogical practice and research.